WRN Protein and Werner Syndrome - Luo, PhD, Jianyuan (North American Journal of Medicine and Science, 2010)
Werner syndrome is an autosomal recessive disorder associated with premature aging and cancer predisposition. Cells from Werner syndrome patients show increased genomic instability and are hypersensitive to DNA damage agents. Werner syndrome is caused by mutations of the WRN gene. WRN protein is a member of RecQ DNA helicase family. It not only contains a conserved 3’-5’ helicase domain as other members of the RecQ family but also contains a unique 3’-5’ exonuclease domain. WRN recognizes specific DNA structures as substrates which are intermediates of DNA metabolism. WRN interacts with many other proteins, which function in telomere maintenance, DNA replication, and DNA repair through different pathways.